PSA is not suitable as a reliable marker for seminal fluid in rectal samples collected post-mortem - Corine Müller; Elie Pascolo Tièche; Martin Zieger (Forensic Science International: Reports, 2025)
Prostate-specific antigen (PSA) tests are used in forensic examinations of sexual offences to indicate the presence of seminal fluid. Based on a retrospective analysis of 484 forensic samples collected in sexual assault cases, we observed a significant enrichment of potentially misleading tests for seminal fluid, for samples collected post-mortem. Reduced reliability of PSA testing for the indication of the presence of ejaculate in samples collected post-mortem has already been reported previously. However, previous studies either included only a small number of rectal samples, particularly from female cadavers, or were based on vaginal swabs. In our study, 34 female and 67 male rectal swab samples collected post-mortem were analysed. The rate of positive SERATEC® PSA Semiquant tests was 33 % for women and 67 % for men. Using male specific qPCR, male DNA was detected in only one of the female samples, indicating a high false-positive rate for both sexes when using SERATEC® PSA Semiquant tests as indicators for the presence of seminal liquid post mortem. Different degrees of decomposition showed no significant correlation with the PSA positivity rate. As expected, a significant correlation between the sex of the deceased individuals and the PSA test result could be demonstrated. The study demonstrates the very limited probative value of PSA as a marker for seminal fluid post mortem.